Perbedaan Pengetahuan Sikap Dan Tindakan Sebelum Dan Sesudah Dilakukan Promosi Kesehatan Melalui Pemutaran Video Tentang CTPS (Studi Dilakukan Pada Siswa SD Negeri 1 Saba, Blahbatuh, Gianyar Tahun 2019) - Dewa Ayu Wulandari; I Ketut Aryana (Poltekkes Kemenkes Denpasar, 2019)
Abstract : Health promotion is very important to improve student knowledge, attitudes, and actions in maintaining their own health. The purpose of this study was to determine differences in knowledge, attitudes, and action before and after health promotion through video screening of CTPS for students at public elementary school 1 Saba. The type of research used is a type of Pre Experimental research type with the One Group Pre-test-Post-test Design. The population in this research is all students of class III and IV. Data using the Wilcoxon test. The result of the research obtained are (p value knowledge = 0,000, attitude = 0,000, and action = 0,000). The conclusion of this study is that there are differences in the knowledge, attitudes, and actions of public elementary school 1 Saba student before and after health promotion through video screening about CTPS. Suggestions that can be given by researchers are for teacher and related agencies to conduct more intensive coaching about hand washing with soap through health promotion programs using video media.